2014
DOI: 10.3171/2014.7.jns132433
|View full text |Cite
|
Sign up to set email alerts
|

Long-term catheter angiography after aneurysm coil therapy: results of 209 patients and predictors of delayed recurrence and retreatment

Abstract: Object Aneurysm recurrence after coil therapy remains a major shortcoming in the endovascular management of cerebral aneurysms. The need for long-term imaging follow-up was recently investigated. This study assessed the diagnostic yield of long-term digital subtraction angiography (DSA) follow-up and determined predictors of delayed aneurysm recurrence and retreatment. Methods Inclusion criteria were as follows: 1) available short-term and long-term (> 36 months) follow-up DSA images, and 2) no or only min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…Male sex as potential factor influencing aneurysm occlusion is unknown related to WEB treatment, but has already been described for conventional coil embolization 22. The association between gender and aneurysm progression has not yet been studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Male sex as potential factor influencing aneurysm occlusion is unknown related to WEB treatment, but has already been described for conventional coil embolization 22. The association between gender and aneurysm progression has not yet been studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Recent studies have revealed that recanalization after coil embolization occurs not only in the short term (typically within 1 year) but also in the long term (after several years). 1,[13][14][15][16] Repeated angiographic examinations or treatments because of the recanalization of coiled aneurysms result in a significant reduction in patient quality of life.…”
mentioning
confidence: 99%
“…In 1 previous study, male sex was also found to be a risk factor for reopening after coiling. 7 Rebleeds occurred in 9 of 106 patients with ruptured basilar tip aneurysms who survived the admission period at time intervals ranging from 4 months to 16.6 years after coiling. In 3 patients, the rebleed was fatal.…”
Section: Discussionmentioning
confidence: 99%
“…1 Risk factors for reopening with time are large aneurysm size, a wide neck, the presence of intraluminal thrombus, low packing attenuation, initial incomplete occlusion, duration of follow-up, and location in the posterior circulation. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] In general, additional coiling is advocated in reopened aneurysms to prevent rebleeding. Most reopenings occur in the first year after coiling and become apparent at the first imaging follow-up after 6 -12 months.…”
mentioning
confidence: 99%
See 1 more Smart Citation